2016
DOI: 10.1093/scan/nsw143
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation for spontaneous and explicit false belief tasks overlaps: new fMRI evidence on belief processing and violation of expectation

Abstract: There is extensive discussion on whether spontaneous and explicit forms of ToM are based on the same cognitive/neural mechanisms or rather reflect qualitatively different processes. For the first time, we analyzed the BOLD signal for false belief processing by directly comparing spontaneous and explicit ToM task versions. In both versions, participants watched videos of a scene including an agent who acquires a true or false belief about the location of an object (belief formation phase). At the end of the mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(110 citation statements)
references
References 65 publications
11
96
1
2
Order By: Relevance
“…All other ROIs showed no significant difference, t s < 1.78, P s > 0.090. Extending on the small group of brain regions identified in initial investigations into spontaneous, belief‐specific implicit ToM abilities [Bardi et al, ; Hyde et al, ; Kovács et al, ; Schneider et al, ], these results demonstrated substantial overlap between the implicit and explicit ToM neural systems and point toward a general system in the brain for belief processing.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…All other ROIs showed no significant difference, t s < 1.78, P s > 0.090. Extending on the small group of brain regions identified in initial investigations into spontaneous, belief‐specific implicit ToM abilities [Bardi et al, ; Hyde et al, ; Kovács et al, ; Schneider et al, ], these results demonstrated substantial overlap between the implicit and explicit ToM neural systems and point toward a general system in the brain for belief processing.…”
Section: Resultssupporting
confidence: 58%
“…Evidence for the role of the TPJ in the implicit ToM system is mixed. Indeed, some studies have found that the right TPJ was more active when a protagonist's belief was a false, relative to a true, reflection of reality [Bardi et al, ; Hyde et al, ; Kovács et al, ), whereas others have failed to find any difference despite using multiple analytic approaches [Schneider et al, ]. The results from this study suggest that the right TPJ is indeed part of the implicit ToM system, as it can detect the presence versus absence of a false belief state.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Given the scarcity of studies investigating the spontaneous ToM system, contradictory findings, and the limited number of participants in each experiment, the present study sought to investigate the above hypotheses using a mega-analytic design in a sample of healthy participants. To this end, we combined data from three previous MRI studies that used the same spontaneous ToM task (in the same MRI scanner) to investigate the neural correlates of spontaneous false belief processing in a bigger sample (Bardi et al, 2017;Hudson, Van Hamme, Maeyens, Brass & Mueller [preprint, bioRxiv]; Nijhof et al, 2018). Using such an approach should result in a sufficiently large sample to overcome the power issue limiting previous findings.…”
Section: Introductionmentioning
confidence: 99%